“Corneal Nerves, CD11c+ Dendritic Cells and Their Impact on Ocular Immune Privilege” - Niederkorn, Jerry Y. (Frontiers in Immunology, 2021)
Many of the ocular tissues necessary for maintaining normal vision have little or no regenerative properties and as a result, unregulated inflammation in the eye can lead to blindness. However, the eye is endowed with a remarkable capacity to restrain immune-mediated inflammation, a condition known as “immune privilege”. Antigens entering the anterior chamber of the eye elicit a unique form of immune regulation called “anterior chamber-associated immune deviation” (ACAID) that culminates in the development of CD8+ T regulatory cells (Tregs) that down-regulate cell- mediated immune effector mechanisms such as cytotoxic T lymphocytes (CTL) and delayed-type hypersensitivity. Corneal allografts are also beneficiaries of ocular immune privilege and enjoy a remarkably high acceptance rate due to the generation of CD4+CD25+ Tregs. However, injury to corneal nerves elicits the release of the neuropeptide substance P (SP), which converts ocular surface CD11c+ dendritic cells to “contrasuppressor” cells that disable both CD8+ ACAID Tregs and CD4+CD25+ corneal allograft-induced Tregs. The loss of ocular immune privilege is an adaptation that allows the full spectrum of immune defense mechanisms that protect the host from life-threatening infections even if the cost is blindness.